Současné možnosti katetrizační implantace mitrální chlopně - Zemánek, David; Hlubocký, Jaroslav; Paleček, Tomáš; Kovárník, Tomáš (Intervenční a akutní kardiologie, 2023)
Transcatheter mitral intervention is one of the most dynamic areas of cardiology. Although the dominant treatment for patients with mitral disease is still cardiac surgery or transcatheter "edge-to-edge" repair, transcatheter mitral valve implantation is an option available for selected patients. The article describes the main anatomical limitations of this method, its current possibilities, as well as perspectives for future development. In the end section, we present the case report of our patient treated successfully with transcatheter implantation of a mitral bioprosthesis.
Keywords: Mitral Valve; mitrální chlopeň; chirurgická náhrada chlopně; srdeční katetrizace; lidé; kardiochirurgické výkony; Cardiac Catheterization; Heart Valve Prosthesis Implantation; Mitral Valve Insufficiency; Cardiac Surgical Procedures; mitrální insuficience; Humans